Lignin for Nano‐ and Microscaled Carrier Systems: Applications, Trends, and Challenges. Issue 10 (13th May 2019) - Sipponen, Mika Henrikki; Lange, Heiko; Crestini, Claudia; Henn, Alexander; Österberg, Monika
Abstract: Invited for this month′s cover is the Review by Mika H. Sipponen and collaborators at Aalto University (Finland), University of Naples Federico II (Italy), and University of Venice Ca' Foscari (Italy). The image shows the versatility of lignins in the fabrication of carrier materials for various active ingredients in nanomedicine, agricultural chemistry, and biocatalysis. The Review itself is available at 10.1002/cssc.201900480 . Abstract : "This Review indicates that lignin‐based materials hold exciting opportunities for a broad range of applications…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201900480 . View the Front Cover here: 10.1002/cssc.201901215 .